2016
DOI: 10.1186/s12916-016-0745-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in chronic kidney disease: a systematic review and meta-analysis

Abstract: BackgroundCognitive impairment is common in people with chronic kidney disease (CKD) and associated with increased morbidity and mortality. Subtle changes can impact engagement with healthcare, comprehension, decision-making, and medication adherence. We aimed to systematically summarise evidence of cognitive changes in CKD.MethodsWe searched MEDLINE (March 2016) for cross-sectional, cohort or randomised studies that measured cognitive function in people with CKD (PROSPERO, registration number CRD42014015226).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
158
2
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(180 citation statements)
references
References 23 publications
9
158
2
11
Order By: Relevance
“…This underlines the importance of identifying individuals with MCI and provide effective interventions to those in a reversible stage of cognitive dysfunction. In addition, an association between renal function and MCI was confirmed in patients with CKD; thus, targeted screening for MCI in this clinical population is important.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This underlines the importance of identifying individuals with MCI and provide effective interventions to those in a reversible stage of cognitive dysfunction. In addition, an association between renal function and MCI was confirmed in patients with CKD; thus, targeted screening for MCI in this clinical population is important.…”
mentioning
confidence: 99%
“…More recently, CKD has also been identified as a risk factor for declining cognitive function and dementia, even at moderate stages of CKD . Poor cognitive function has been linked to poor health literacy, poor medication adherence, worse physical and mental health, and greater morbidity and mortality . In addition, CKD‐related cognitive impairment affects healthcare decision‐making .…”
mentioning
confidence: 99%
“…Furthermore, orientation, attention, and language are affected. The cognitive impact of CKDs is likely to diminish the capacity of patients to engage with healthcare decisions [13]. Considering the high prevalence of hypertension, heart disease, and CKDs in patients with type 1 DM, these comorbidities could contribute to the link between type 1 DM and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the recommendation against routine screening is that the majority of older people with mild cognitive impairment do not progress to dementia or that their cognitive function may even improve. However, there is compelling evidence that cognitive impairment occurs early in ESKD [64] and that people on dialysis have worse cognition than the general population [5,64]. Further, in a recent study of dialysis patients with cognitive impairment, there is evidence that cognition declines faster, with effects on the decision-making capacity [68].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in inclusion and exclusion criteria, depending on the purpose of the study, may also explain the variable prevalence. While the prevalence of cognitive impairment in people on dialysis is not clear, 2 systematic reviews found that people with ESKD with or without dialysis consistently had lower scores, indicating a high likelihood of cognitive impairment [5,64]. …”
Section: Discussionmentioning
confidence: 99%